The Emerald handbook of quantum storytelling consulting - Boje, David M.; Sanchez, Mabel (Emerald Publishing Limited, 2019)
This Handbook develops a practical understanding of the new quantum storytelling consulting paradigm, providing case examples, ways to enact practices, and methods to conduct research into its impact and consequences. It will be essential reading for all scholars and practitioners of story and narrative consulting.